New technologies and their implications in the process of encouraging reading and writing - Acevedo Colmenares, Karina; Ramirez Rueda, Claudia Rocio; Atuesta Diaz, Martha Azucena (Rastros Rostros, 2002)
In this new century, reading and writing abandon the old schemes and concepts to give way and undertake the development of skills necessary to use new technologies in teaching, since the great expectation of computer science is located in those educational modalities that promote the use of mass media and tools for education in the classroom.